Quasi-freestanding AA-stacked bilayer graphene induced by calcium intercalation of the graphene-silicon carbide interface - Grubišić-Čabo, Antonija; Kotsakidis, Jimmy C.; Yin, Yuefeng; Tadich, Anton; Haldon, Matthew; Solari, Sean; Riley, John; Huwald, Eric; Daniels, Kevin M.; Myers-Ward, Rachael L.; Edmonds, Mark T.; Medhekar, Nikhil V.; et al. (Frontiers in Nanotechnology, 2024)
We study quasi-freestanding bilayer graphene on silicon carbide intercalated by calcium. The intercalation, and subsequent changes to the system, were investigated by low-energy electron diffraction, angle-resolved photoemission spectroscopy (ARPES) and density-functional theory (DFT). Calcium is found to intercalate only at the graphene-SiC interface, completely displacing the hydrogen terminating SiC. As a consequence, the system becomes highly n-doped. Comparison to DFT calculations shows that the band dispersion, as determined by ARPES, deviates from the band structure expected for Bernal-stacked bilayer graphene. Instead, the electronic structure closely matches AA-stacked bilayer graphene on Ca-terminated SiC, indicating a spontaneous 1 Grubi ši ć-Čabo et al.transition from AB-to AA-stacked bilayer graphene following calcium intercalation of the underlying graphene-SiC interface.